Implementasi Pelayanan Terpadu Satu Pintu (PTSP) transformasi digital di Kementerian Agama Kabupaten Malang - Syofa, Dewi Adilah Nada (Maliki Interdisciplinary Journal, 2024)
The government adopts a One-Stop Integrated Service (PTSP) policy in responding to public complaints as service users, with the legal basis of one-stop integrated services contained in the Minister of Home Affairs Regulation No. 24 of 2006 concerning Guidelines for the Implementation of One-Stop Integrated Licensing Services. The purpose of the establishment of one-stop integrated services is "to improve the quality of public services and provide wider access to the public to obtain public services. The method used in this article is qualitative descriptive with a case study on the One Stop Integrated Service (PTSP) division of Digital Transformation of the Ministry of Religious Affairs of Malang Regency. This research emphasizes how the implementation of one-stop integrated services (PTSP) digital transformation and analysis of the PTSP. This data collection technique is through interviews, observation, and documentation. One-Stop Integrated Service or abbreviated as PTSP is to facilitate and provide certainty to the community in getting services. PTSP is a government innovation program in order to approach and improve public services to the community and as an effort to create services that are fast, easy, certain, transparent, affordable, and realize good governance. With the existence of PTSP, this Digital Transformation has run in accordance with the expectations of the Head of the Office of the Ministry of Religious Affairs of Malang Regency and the community. That is the goal of providing the best service for the community that is easy, fast, precise, academic and free.